(untitled) (Trento Student Law Review, 2025)
This article explores the relationship between copyright law and automated enforcement technologies on digital platforms. The constitutional foundation of copyright, the doctrine of fair use, secondary liability, and the DMCA safe harbor provisions incentivize platforms to develop and utilize such technologies. YouTube’s ContentID system is thereby used as an emblematic example of this interaction. The first part of the paper outlines these foundational aspects, providing a legal framework for understanding how copyright law has evolved to address digital challenges. It discusses the constitutional basis for copyright protection – which creates the legal basis to grant creators exclusive rights – and examines the fair use doctrine that balances copyright holders’ rights with users’ interests. The article also considers the legal implications of secondary liability for infringing content and the DMCA’s safe harbor provisions, which offer protections for platforms hosting user-generated content. In the second part the paper builds on this legal framework by analyzing contemporary issues in online copyright enforcement. The rapid rise of automated systems, like YouTube’s ContentID, has transformed how digital platforms monitor and enforce copyright, but it has also raised concerns regarding fairness, accuracy, and overreach, which negatively impact on user’s rights. This section highlights these challenges and proposes potential solutions to enhance the effectiveness and equity of copyright enforcement in the digital age, ensuring both creators’ rights and users’ freedoms are fairly protected.